Zakat and Sustainable Development: A Green Campus Funding Model Based on Maqāṣid al-Sharī‘ah - Zulkifli, Zulkifli; Khairunisa, Madona; Megawati, Devi; Mochammad Sahid, Mualimin (An-Nida', 2026)
Zakat possesses considerable strategic potential as a social financing instrument to support sustainable development within State Islamic Higher Education Institutions (PTKIN). Nevertheless, its application in the advancement of green campuses remains suboptimal and has been insufficiently explored from the perspectives of sustainable economics and maqāṣid al-syarī‘ah. This study seeks to examine the role of zakat as an innovative funding source for developing a green campus ecosystem that aligns with both sustainability principles and Islamic values. The urgency of this research stems from the necessity for an alternative financing model capable of enhancing campus environmental governance while promoting the sustainability of Islamic higher education. Employing a qualitative methodology, this study utilises library research and thematic analysis of literature pertaining to zakat, the green economy, and campus management policies. The findings highlight three principal points. First, professional zakat demonstrates significant potential as a sustainable financing mechanism via an endowment fund, particularly within PTKIN. Second, the zakat-based green campus model is conceptualised through a maqāṣid al-syarī‘ah framework encompassing faculty capacity building, optimisation of campus spaces and land use, sustainable funding support, and the empowerment of mustahiq students. Third, the implementation of zakat-based programmes contributes to sustainable economic development, the strengthening of entrepreneurship, and the enduring sustainability of higher education. This study contributes to the development of a sustainability-oriented concept of Islamic social finance aimed at advancing Islamic higher education.